Culture of five species of Malaysia indigenous freshwater microalgae - Sallehudin, Nor Jannah; Mustapa, Mokhzanni; Mel , Maizirwan; Ahmad Raus, Raha (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Five species of Malaysia indigenous chlorophycean microalgae were grown in laboratory culture under the comparable environmental condition and the population doubling time (td) as well as maximum growth rate (μmax) each was evaluated. Using batch culture operation grown under the photoheterotrophic condition, the growth rate of Chlorella sp. B, Chlorella sp. TLL, Scenedesmus obliquus TLL, Ankistrodesmus sp. TH and Scenedesmus sp. TH is 0.102 hr-1, 0.095 hr-1, 0.044 hr-1, 0.03 hr-1 and 0.011 hr-1 respectively, while the doubling time is 6.8 hr-1 (Chlorella sp. B), 7.3 hr-1 (Chlorella sp. TLL), 15.75 hr-1 (Scenedesmus obliquus TLL), 23.1 hr-1 (Ankistrodesmus sp. TH) and 63.01 hr-1 (Scenedesmus sp. TH). The growth of Chlorella can be seen materially faster than any other microalgae strain especially from the strain that has spines such as Scenedesmus sp. TH. Based on the observations available, it appears that smaller strains of unicellular microalgae have appreciably higher intrinsic growth rates than algae of the larger size.